Habitat and Population Structure of Javan Langurs (Trachypithecus auratus auratus) at Gunung Celering Nature Reserve, Jepara Regency Central Java - Santoso, Budi; Muali, Muali; Thamrin, Ricky; Ardiana, Putut Trisna; Adi, Danang Setyo (Badan Pengembang Konservasi UNNES, 2023)
A lot of information has been conveyed by the people around the Gunung Celering Nature Reserve regarding encounters with the Javan Langurs (Trachypithecus auratus auratus). Research on the Javan langurs (Trachypithecus auratus auratus) in the Gunung Celering Nature Reserve which is located at Donorojo District, Jepara Regency was carried out on 14-31 August 2023. This research aims to determine the population of the Javan Langur, its population distribution at the Gunung Celering Nature Reserve and to find out the the type of habitat where it is located the javan langur was encountered.During the observations, 109 individuals of Javan Langur were encountered from 12 groups at 8 different observation locations. Of the 109 individuals, it showed that 39% of them were adult Javan Langurs, 43% were juveniles and 17% were children with a population density of 0.08 individuals/ha and a sex ratio of 1:1.5. The Javan Langur habitat at Gunung Celering nature Reserve consists of 35 tree species at the observation area and 21 of which have potential as javan Langur food.